КРОТАЛАРИЯ (CROTALARIA JUNCEA) НИНГ ҚУРУҚ МАССА ОҒИРЛИГИГА ЭКИШ МУДДАТ ВА МЕЪЁРЛАРИНИ ТАЪСИРИ - Нуруллаева , Манзура Шавкатовна; Негматова , Сурайё Тешаевна (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
This article highlights the importance of non-traditional leguminous crop Crotalaria juncea in agriculture and the effect of timing and norms of planting on the dry weight of the plant.Scientifically proven that to increase the dry weight of crotalaria in the third decade of April (20-25.04) 10 kg / ha, and to add dry weight 1 ha - 14 kg / ha - the optimal time and rate to get an abundant harvest.